1968
DOI: 10.1111/j.1464-410x.1968.tb09898.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyelo-Duodenal Fistula

Abstract: SUMMARY A case of spontaneous pyelo‐duodenal fistula is described and is the twenty‐fourth so far recorded in the Iiterature. It is the first case to have survived without surgical ablation of the fistula immediately following the diagnosis. The symptomatology and treatment of the condition are briefly reviewed. Ail previously reported cases are listed in table form to correlate the setiology, management and prognosis. Analysis of the cases suggests that although definitive surgery is the treatment of choice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Pyeloduodenal fistula, first described in 1841 by Rayer and Campaignac, is an uncommon clinical entity. 6 7 The anatomic proximity of the right kidney with the second portion of the duodenum enables fistula formation in the setting of renal inflammatory conditions, including nephrolithiasis or pyelonephritis. Malignant aetiologies of pyeloduodenal fistula include urothelial carcinoma, renal transitional cell carcinoma and nephrolithiasis-related squamous cell carcinoma and adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Pyeloduodenal fistula, first described in 1841 by Rayer and Campaignac, is an uncommon clinical entity. 6 7 The anatomic proximity of the right kidney with the second portion of the duodenum enables fistula formation in the setting of renal inflammatory conditions, including nephrolithiasis or pyelonephritis. Malignant aetiologies of pyeloduodenal fistula include urothelial carcinoma, renal transitional cell carcinoma and nephrolithiasis-related squamous cell carcinoma and adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Only eight cases of pyeloduodenal fistulas were due to upper tract malignancy (Table-I). [2][3][4][5][6][7][8][9] Most pyeloduodenal fistulas occur because of a chronic renal inflammatory disease, such as pyonephrosis, perinephritis, renal calculi, xanthogranulomatous pyelonephritis, or tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the review by McEwan, 1 it was pointed out that an insidious and progressive asymptomatic pyelonephritis was an attendant clinical condition, but the gastrointestinal symptoms should be considered an important clue for diagnosis. There are several reviews that have reported that diarrhea, nausea, vomiting, epigastric pain, dyspepsia, general malaise and weight loss are common symptoms, but there was only one reported case of presentation with melena.…”
Section: Discussionmentioning
confidence: 99%
“…Organic obstruction of the duodenum is rare and the combination of duodenal and common bile duct obstruction caused by renal sepsis and associated with a pyelo-duodenal fistula has not been reported previoudy. McEwan (1968) reviewed 24 cases of spontaneous pyelo-duodenal fistula in the world literature and discussed aetiology and nianagement. Patients usually present with nonspecific gastro-intestinal symptonis which :trc associated with chronic renal sepsis and a l s o on occasions the flow of urine into thc duodenum gives rise to a hyperchloraemic acidosis (Boggs, Blundon and Davis.…”
Section: Commentmentioning
confidence: 99%